2016
DOI: 10.1209/0295-5075/113/37002
|View full text |Cite
|
Sign up to set email alerts
|

Charge and spin density in the helical Luttinger liquid

Abstract: -The weakly interacting helical Luttinger liquid, due to spin momentum locking, is characterized by extremely peculiar local observables: we show that the density-density correlation functions do not exhibit signatures of Friedel and Wigner oscillations, and that spin-spin correlation functions, which are strongly anisotropic, witness the formation of a planar spin wave. Moreover, we demonstrate that the most relevant scattering potentials involving a localized impurity are not able to modify the electron dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…For non-interacting case K = 1 while 0 < K < 1 (K > 1) corresponds to repulsive (attractive) electronic interactions. Also, we have assumed that the interactions are weak enough to ignore backscattering potential [76,77]. Note, however, that it has been shown that elastic spin-flip backscattering can be occurred by coupling of electrons to nuclear spins through the hyperfine interaction causing a significant edge resistance at low enough temperatures [56].…”
Section: Obtain the Low-energy Hamiltonian Asmentioning
confidence: 99%
“…For non-interacting case K = 1 while 0 < K < 1 (K > 1) corresponds to repulsive (attractive) electronic interactions. Also, we have assumed that the interactions are weak enough to ignore backscattering potential [76,77]. Note, however, that it has been shown that elastic spin-flip backscattering can be occurred by coupling of electrons to nuclear spins through the hyperfine interaction causing a significant edge resistance at low enough temperatures [56].…”
Section: Obtain the Low-energy Hamiltonian Asmentioning
confidence: 99%